Differential polypeptide synthesis of the proton-translocating ATPase of Escherichia coli. - Brusilow, W S (1982)
We investigated the regulation of the synthesis of the eight polypeptides of the Escherichia coli proton-translocating ATPase. A plasmid carrying the eight genes of the unc operon was used to direct in vivo and in vitro protein synthesis of the eight polypeptides. Analysis of these data indicates that the ATPase polypeptides are synthesized in unequal amounts both in vitro and in vivo. We identified several regions within the unc operon at which expression of a gene is either increased or decreased from that of the preceding gene. Since genetic information indicates a single polycistronic mRNA for all eight genes of this operon, the observed differential synthesis of the polypeptides is most likely the result of translational regulation. The effect of varying the temperature suggests that the secondary structure in the mRNA may affect the rate of translation initiation in the region between uncE and uncF.